Distribution and conservation status of nominate Euptychia cesarense in the East Andes of Colombia - Huertas, Blanca; Fagua, Giovanny (Zootaxa, 2011)
In this issue of Zootaxa, Pulido et al. (2011) describe a new species of butterfly based on disjunct populations in the northern East Andes of Colombia, Ecuador and Peru. The East Andes population (nominate subspecies) of this new species was previously found in Serranía de los Yariguíes, Santander, Colombia in January 2003. A photograph of a specimen was illustrated as "Euptychia sp. nov." in Huertas (2004, Appendix 1, Plate 5; also listed in Appendix 3, p. 5) and this photograph was discussed with Pulido in 2008. The species was also reported as "Euptychia sp. nov." in Huertas & Arias (2005, p. 75) and, following discussions with other specialists, it was reported as "Pharneuptychia sp." in Huertas & Ríos (2006, p. 145). Various other new taxa have been described or have descriptions underway following expeditions in Serranía de los Yariguíes (e.g. Donegan & Huertas 2006; Huertas & Arias 2007; Huertas et al. 2009; Huertas & Fagua MS). Four other specimens of E. cesarense were found at MPUJ, collected in 2004.